Genetic Polymorphisms of Toll-like receptors 2 and 9 as Susceptibility Factors for the Development of Ankylosing Spondylitis and Psoriatic Arthritis - Camila F. Oliveira-Toré; Amarilis G. Moraes; Gabriela F. Martinez; Janisleya S. F. Neves; Luciana C. Macedo; Marco A. Rocha-Loures; Marília G. Quirino; Hugo V. Alves; Ana M. Sell; Jeane E. L. Visentainer (Journal of Immunology Research)
Introduction. Ankylosing spondylitis (AS) and psoriatic arthritis (PsA) are classified as spondyloarthritis (SpA), a group of inflammatory rheumatic diseases with complex genetic etiology. Toll-like receptors (TLRs) have an important role in the mechanism of innate immunity and may influence inflammatory responses. Polymorphisms in TLR genes that lead to changes in these receptors or that interfere with the transcription rates of mRNA TLR may be involved in the chronic inflammatory immune response observed in SpA. Currently, there is a lack of studies associating genetic polymorphisms in TLRs and SpA. Objective. Therefore, this case-control study is aimed at analyzing the influence of the respective SNPs on TLR2 rs5743708, TLR6 rs5743810, and TLR9 rs5743836 and rs187084 in the immunopathogenesis of SpA. Methods. The polymorphisms genotyped by PCR-RFLP were TLR2 rs5743708, TLR6 rs5743810, and TLR9 rs5743836 and rs187084. The HLA-B∗27 was performed by PCR-SSP. Results. Logistic regression analysis showed a strong association between SNPs in TLR2 and TLR9 and susceptibility to SpA (OR=12.56; CI=6.5-25.9 and OR=1.62; CI=1.20-2.21, respectively). No association was observed among HLA-B∗27 and TLR polymorphisms (p=0.72), nor among BASDAI and TLR polymorphisms (p=0.85). Discussion. Our findings suggest that polymorphisms in TLR2 and TLR9 genes may contribute to the immunopathogenesis of the SpA. The rs187084, rs5743836, and rs5743708 polymorphisms were associated with the risk of SpA development, in this study, and lead to significant changes in the innate and adaptive immune response profile, as well as the maintenance of the regulation of immunological mechanisms. Conclusion. The polymorphism rs5743708 for the TLR2 and the rs187084_rs5743836 TLR9 haplotypes appear to be involved in the development of clinical forms of SpA and can be a possible therapeutic target for the spondyloarthritis.